Intelligence and Imperial Defence : British Intelligence and the Defence of the Indian Empire 1904-1924 - Popplewell, Richard J. (London Frank Cass, 1995)
This is an account of the British intelligence operations based in both India and London, which defended the Indian Empire against subversion during the first two decades of the 20th century.
Include Glossary, Bibliography and Index
Keywords: India -- Politics and government